Biochemical characterization and chemical validation of Leishmania MAP Kinase-3 as a potential drug target - Raj, Shweta; Saha, Gundappa; Sasidharan, Santanu; Dubey, Vikash Kumar; Saudagar, Prakash (Nature Publishing Group, 2019)
Protozoan parasites of the Leishmania genus have evolved unique signaling pathways that can sense various environmental changes and trigger stage differentiation for survival and host infectivity. MAP kinase (MAPK) plays a critical role in various cellular activities like cell differentiation, proliferation, stress regulation, and apoptosis. The Leishmania donovani MAPK3 (LdMAPK3) is involved in the regulation of flagella length and hence plays an important role in disease transmission. Here, we reported the gene cloning, protein expression, biochemical characterizations, inhibition studies and cell proliferation assay of LdMAPK3. The recombinant purified LdMAPK3 enzyme obeys the Michaelis-Menten equation with Km and Vmax of LdMAPK3 was found to be 20.23 nM and 38.77 ± 0.71 nmoles ATP consumed/mg LdMAPK3/min respectively. The maximum kinase activity of LdMAPK3 was recorded at 35 °C and pH 7. The in-vitro inhibition studies with two natural inhibitors genistein (GEN) and chrysin (CHY) was evaluated against LdMAPK3. The Ki value for GEN and CHY were found to be 3.76 ± 0.28 µM and Ki = 8.75 ± 0.11 µM respectively. The IC50 value for the compounds, GEN and CHY against L. donovani promastigotes were calculated as 9.9 µg/mL and 13 µg/mL respectively. Our study, therefore, reports LdMAPK3 as a new target for therapeutic approach against leishmaniasis. © 2019, The Author(s).
Keywords: Biochemical characterization; Leishmania MAP Kinase-3; Chemical validation; Potential drug target